The Garuda Strikes Back : Indonesian Economic Diplomacy to Tackle European Union Protectionism on Crude Palm Oil - Ichlas El Qudsi, Mohammad; Kusumawardhana, Indra; Kyrychenko, Volodymyr (Journal of International Relations on Energy Affairs, 2020)
This paper analyzes Indonesia's economic diplomacy efforts in overcoming trade barriers to Indonesian palm oil commodities carried out by the European Union. Until now, the Indonesian Crude Palm Oil (CPO) industry has experienced tremendous pressure from the European Union (EU) as one of the main export destinations for Indonesian CPO. In order to secure Indonesia's national interests, instead of taking a cooperative approach, the Indonesian government has responded to the EU's discriminatory attitude towards palm oil commodities with a series of assertive economic diplomacy approaches. This assertive economic diplomacy approach is understood by this paper as a form of the â€œPower-Play Endâ€ strategy articulated by Indonesia to secure its national interests in mainland Europe. The main question in this paper that will be answered is how can Indonesia use this strategy in overcoming trade barriers imposed by the EU on palm oil commodities? Using the concept of Economic Diplomacy which emphasizes three elements, namely the use of political influence and relations, the use of economic assets, the consolidation of the political climate and the international environment - this paper will examine Indonesia's economic diplomacy maneuver in related issues.